La Ciutat de Repòs i Vacances - Julie Roland (Mélanges de la Casa de Velázquez)
In 1933 the GATCPAC, a group of architects of the modern school during the Second Spanish Republic, presented plans for a Ciutat de Repòs i Vacances for the city of Barcelona. The plan, covering 8 km of beach south of the Catalan capital, was the star project of this group of architects, envisaging the construction of a new town that would provide a place of repose for the toiling masses. This was no mere architectural plan; the proposal as presented also reflected a political and social programme in response to the economic crisis then afflicting the country. The point of this article then is to understand the place of this project in Catalan political life and the theoretical input of the Ciutat de Repòs i Vacances to international debates among architects of the modern movement. Moving beyond a regionalist context, the article seeks to grasp the supra-national scope of this Catalan project.